PEMBELAJARAN MORAL MELALUI MATA KULIAH HUKUM ISLAM - Marjuki Marjuki (Universitas Negeri Yogyakarta, 2008)
The main problems in this study are how moral learning is achieved by the Islamic Law subject in the PPKN Department (now: PKnH) of the Social Science Faculty (now: FISE) ofYogyakarta State University and what factors influence moral learning in the Islamic Law subject. The study is qualitative and descriptive survey research. The data were obtained by questionnaires and interviews with the students taking the Islamic Law subject. The results show that Islamic law learning is one of the moral learning. The moral learning achieved through the Islamic Law subject manifests in many ways, i.e.: 1) Almost all instructional topics contain moral values, 2) Learning strategies which endorse moral problems are the dialogue and speech method and the discussion method, and 3) The assessment process which endorses moral problems is that related to the students' behaviours and attitudesfrom the beginning until the end of the learning process. The main factors obstructing the moral learning are: 1) The basic competence of students in PPKN is heterogeneous, 2) The students' interest in moral problems is not high, and 3) Moral learning is difficult.